Pengaruh Strategi Pemasaran dan Marketing Communication terhadap Brand Awareness dan Dampaknya pada Minat Menonton RCTI (Rajawali Citra Televisi Indonesia) - Dwitama, Aldio; Rita, Rita (Bina Nusantara University, 2015)
At the age of 24, in 2013 (the period of January to December 2013), Rajawali Citra Televisi Indonesia (RCTI) has been retaining the position of market leader with a 17.8% audience share reached. Based on that, RCTI needs to maintain to foster and expand the public watching interest on their program. This study aims to determine the effect of marketing strategy and marketing communications on brand awareness and the impact on the public watching interest on their program. The method used is associative-survey research methods. Data collection techniques are done by using a questionnaire distributed to the public viewers of RCTI and by making interviews to the Senior Manager. Data analysis techniques used is path analysis. As a result, there is a positive and significant effect of the variables of marketing strategy and marketing communications on brand awareness and the impact on public watching interest on RCTI.